The Development of Legal Word Units in Armenian According to Ghazar Parpetsi’s Work "History of Armenia" (A Synchronic-Diachronic Analysis) - Karapetyan, Sirarpi (ՀՀ ԳԱԱ)
The lexical stock of any language as its constituent part immediately reflects changes in the social and scientific life of its speakers, i. e. it expresses the changes and evolution of the language itself over time. Every new phenomenon appearing in science, technology, social life, etc. gets its verbal expression at once, which enriches the vocabulary of the language, and legal language is no exception. In its turn, the emergence of new terms happens due to the continuous development and improvement of the vocabulary of the language. These newly coined terms often become established, rooted in the language just as ordinary words and, in this way, make its vocabulary richer. Ցանկացած լեզվի բառային կազմը՝ որպես դրա անբաժանելի մաս, ուղղակիորեն արտացոլում է լեզվակիրների հասարակական և գիտական կյանքում տեղի ունեցող փոփոխությունները։ Այլ կերպ ասած՝ այն անմիջապես արտացոլում է լեզվի փոփոխությունը և զարգացումը։ Գիտության, տեխնիկայի բնագավառում, հասարակական կյանքում ի հայտ եկած յուրաքանչյուր նոր երևույթ անմիջապես արտահայտվում է լեզվում՝ հարստացնելով դրա բառապաշարը։ Իր հերթին նոր եզրույթների առաջացումը տեղի է ունենում լեզվի բառապաշարի մշտական փոփոխության և հարստացման եղանակով։ Նորաստեղծ այս եզրույթները հաճախ արմատավորվում են լեզվում այնպես, ինչպես սովորական բառերը և դրանով իսկ հարստացնում այն: Лексический состав любого языка как его составная часть непосредственно отражает изменения, происходящие в общественной и научной жизни носителей данного языка. Каждое новое явление, появляющееся в науке, технике, общественной жизни и т. д., немедленно получает свое словесное выражение, что обогащает словарный запас определенного языка. В свою очередь, появление новых терминов происходит за счет постоянного изменения и обогащения словарного запаса языка. Эти новообразованные термины часто укореняются в языке так же, как и обычные слова, и тем самым обогащают его словарный запас.
Keywords: Social and Humanitarian Sciences